2023
DOI: 10.3390/ijms241612601
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Non-Clinical Cardiovascular Disease Associated Pathologies in Parkinson’s Disease

Abstract: Despite considerable breakthroughs in Parkinson’s disease (PD) research, understanding of non-motor symptoms (NMS) in PD remains limited. The lack of basic level models that can properly recapitulate PD NMS either in vivo or in vitro complicates matters. Even so, recent research advances have identified cardiovascular NMS as being underestimated in PD. Considering that a cardiovascular phenotype reflects sympathetic autonomic dysregulation, cardiovascular symptoms of PD can play a pivotal role in understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Previous studies have confirmed that α-synuclein was detectable within the heart and cardiovascular autonomic failure was a common symptom in α-synucleinopathies [ 47 , 48 ]. The α-synuclein in heart may further contributed to myocardial disorders, including cardiomyopathy, septal fibrosis, and ventricular hypertrophy [ 49 ]. However, the underlying mechanisms that RBD contributed to HF need further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that α-synuclein was detectable within the heart and cardiovascular autonomic failure was a common symptom in α-synucleinopathies [ 47 , 48 ]. The α-synuclein in heart may further contributed to myocardial disorders, including cardiomyopathy, septal fibrosis, and ventricular hypertrophy [ 49 ]. However, the underlying mechanisms that RBD contributed to HF need further exploration.…”
Section: Discussionmentioning
confidence: 99%